Mass and energy balance of the carbonization of babassu nutshell as affected by temperature - Protásio, Thiago de Paula; Trugilho, Paulo Fernando; Napoli, Alfredo; Silva, Marcela Gomes da; Couto, Allan Motta (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the carbonization yield of babassu nutshell as affected by final temperature, as well as the energy losses involved in the process. Three layers constituting the babassu nut, that is, the epicarp, mesocarp and endocarp, were used together. The material was carbonized, considering the following final temperatures: 450, 550, 650, 750, and 850°C. The following were evaluated: energy and charcoal yields, pyroligneous liquid, non‑condensable gases, and fixed carbon. The use of babassu nutshell can be highly feasible for charcoal production. The yield of charcoal from babassu nutshell carbonization was higher than that reported in the literature for Eucalyptus wood carbonization, considering the final temperature of 450°C. Charcoal and energy yields decreased more sharply at lower temperatures, with a tendency to stabilize at higher temperatures. The energy yields obtained can be considered satisfactory, with losses between 45 and 52% (based on higher heating value) and between 43 and 49% (based on lower heating value) at temperatures ranging from 450 to 850°C, respectively. Yields in fixed carbon and pyroligneous liquid are not affected by the final carbonization temperature.